THE PHONOLOGY INTERFERENCE OF BAHASA BATAK IN ENGLISH PREACHING DELIVERED BY THE PRIEST OF HKBP YOGYAKARTA CHURCH - Saragi, Devi Melisa (JOURNAL OF ADVANCED ENGLISH STUDIES, 2018)
This research intends to describe the interference of vowels and consonants of Bahasa Batak Toba in English preaching and to explain the factors which can cause the interferences. The data were collected through interview, observation and recordings of English preach delivered by the priests. After the data were sufficient, the recordings were transcribed into the orthographic transcription and continued tobe transcribed into the phonetic transcription based on the priests’ utterances and then compared to IPA in order to get the form of the interferences in vowels and consonants. The results of this research are that: 1) the interferences of Batak Toba in pronouncing the English vowels were [i], [ɪ], [æ], [ə], [ʌ], [ɒ], [ɔ:], [ʊ], [u:], [ɜ:], diphtong dan triftong, while the interferences of Batak Toba in pronouncing the English consonants were [p], [b], [t], [d], [k], [g], [ʧ], [f], [v], [θ], [ð], [z], [ʃ], [ʒ], consonant clusters in the form of –VCC and –VCCC. 2) The factors which cause the interferences are linguistics factors and nonlinguistic factors.